Pengaruh Penyuluhan Sarapan Pagi Terhadap Kadar Hemoglobin dan Pengetahuan pada Siswi MAN 2 Aceh Tamiang - Nababan, Agnes Sry Vera; Wanda Lestari; Eka Nenni Jairani; Yulita, Yulita; Salsabila, Wan Indah (Kabar Gizi Indonesia, 2023)
Female students are at risk for anemia, and one of the reasons of anemia is not having breakfast. Knowledge is one of the variables that impact schoolchildren's breakfast. The study aimed to see how breakfast counseling affects the hemoglobin levels and knowledge of students at MAN 2 Aceh Tamiang. This study was pre-experimental, using a one-group pre-test and post-test design. The Wilcoxon analysis test was used to evaluate the data.According to the Wilcoxon analysis test results, the breakfast counselingvariable on hemoglobin levels has a P value of 0.001, indicating that there was an effect of breakfast counseling on hemoglobin levels, whereas the breakfast counseling variable on knowledge has a p-value of 0.000, indicating that there was no effect of breakfast counseling on knowledge. There is a significant effect between breakfast counseling on hemoglobin levels and knowledge of students at MAN 2 Aceh Tamiang.